Durability of SVR in chronic hepatitis C patients treated with peginterferon‐α2a/ribavirin in combination with a direct‐acting anti‐viral. Issue 2 (26th May 2013) - Rutter, K.; Hofer, H.; Beinhardt, S.; Dulic, M.; Gschwantler, M.; Maieron, A.; Laferl, H.; Stättermayer, A. F.; Scherzer, T.‐M.; Strassl, R.; Holzmann, H.; Steindl‐Munda, P.; et al.
Summary Background The introduction of direct‐acting anti‐virals has increased sustained virological response (SVR) rates in chronic hepatitis C genotype 1 infection. At present, data on long‐term durability of viral eradication after successful triple therapy are lacking. Aim To evaluate the long‐term durability of viral eradication in patients treated with triple therapy, including direct‐acting anti‐virals. Methods Patients who participated in randomised, controlled trials or an extended access programme of treatment with peginterferon‐α2a/ribavirin in combination with a direct‐acting anti‐viral (telaprevir, danoprevir, faldaprevir, simeprevir, mericitabine, balapiravir) were followed after achieving SVR. The median follow‐up after the patients was 21 (range: 7–64) months. Results One hundred and three patients with chronic hepatitis C genotype 1 infection [f/m: 34/69; GT‐1b: 67 GT‐1a: 34, GT‐4: 2; mean age: 47.6 years (45.5–49.7; 95% CI)] achieving a SVR triple therapy were followed. Two cases of late relapses (2/103, 1.9%; 95% CI: 0.24–6.8) were observed. One patient was cirrhotic, both carried the genotype 1b and completed the prescribed treatment. The relapses occurred 8 and 12 months after cessation of anti‐viral treatment. Cloning sequencing revealed identical sequence in both patients. Resistance analysis revealed no presence of viral resistance. Conclusion Like the SVR after peginterferon‐α2/ribavirin combination treatment, HCV eradication after triple therapy remains durable after long‐term follow‐up.